2013
DOI: 10.1186/1471-2296-14-92
|View full text |Cite
|
Sign up to set email alerts
|

GP perspectives of irritable bowel syndrome – an accepted illness, but management deviates from guidelines: a qualitative study

Abstract: BackgroundThe estimated prevalence of irritable bowel syndrome (IBS) is 10%. Up to one third of patients develop chronic symptoms, which impact on everyday functioning and psychological wellbeing. Guidelines suggest an increased role for primary care in the management of patients with IBS, and referral for psychological interventions. Literature reports dissatisfaction and frustration experienced by both patients with IBS and healthcare professionals. The aim of this study was to explore the perspectives of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…Findings from our qualitative study suggest GPs did not describe difficulties in managing patients with IBS [6]. This is also evident in the current study where a relatively small proportion of patients with IBS had a referral to a GI specialist, compared to those patients with a diagnosis of IBD.…”
Section: Discussionsupporting
confidence: 65%
“…Findings from our qualitative study suggest GPs did not describe difficulties in managing patients with IBS [6]. This is also evident in the current study where a relatively small proportion of patients with IBS had a referral to a GI specialist, compared to those patients with a diagnosis of IBD.…”
Section: Discussionsupporting
confidence: 65%
“…12 This is also supported by the reluctance of PHCPs to add IBS read-codes to patient records until more serious pathology was excluded. 31 Although FGIDs are largely managed in primary care, this study together with the specialist FGID referral load suggests that the real-world confidence of clinicians in diagnosing FGIDs and communicating in some instances is low.…”
Section: Discussionmentioning
confidence: 88%
“…Only 52% of gastroenterologists and 34% of PHCPs were confident diagnosing IBS based on symptoms, history and physical exam, with less than half of these confident to inform the patient without further investigations . This is also supported by the reluctance of PHCPs to add IBS read‐codes to patient records until more serious pathology was excluded . Although FGIDs are largely managed in primary care, this study together with the specialist FGID referral load suggests that the real‐world confidence of clinicians in diagnosing FGIDs and communicating in some instances is low.…”
Section: Discussionmentioning
confidence: 93%
“…Although clinical trial data support that the reduction of FODMAPs is beneficial for patients with IBS [52,54,57], long-term adherence to a strict low FODMAP diet is not recommended because of nutritional concerns and potential effects on the gut microbiota [58]; rather, excluded components of the diet should be slowly reintroduced until satisfactory symptom control is maintained by the individual patient [59]. Interestingly, a study conducted in England reported that primary care physicians (PCPs) generally recommend dietary modification first to patients with IBS [60], but based on the very low quality of evidence, the American College of Gastroenterology (ACG) makes only a weak recommendation for specialized diets in the management of IBS [1].…”
Section: Low Fodmap Dietmentioning
confidence: 99%